2010
DOI: 10.1111/j.1742-4658.2010.07798.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans in health and disease: the multiple roles of syndecan shedding

Abstract: Proteolytic processes in the extracellular matrix are a major influence on cell adhesion, migration, survival, differentiation and proliferation. The syndecan cell‐surface proteoglycans are important mediators of cell spreading on extracellular matrix and respond to growth factors and other biologically active polypeptides. The ectodomain of each syndecan is constitutively shed from many cultured cells, but is accelerated in response to wound healing and diverse pathophysiological events. Ectodomain shedding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
279
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 277 publications
(284 citation statements)
references
References 123 publications
4
279
0
1
Order By: Relevance
“…Syndecan shedding is highly regulated and dependent on the so-called sheddase enzymes. 188 In Paper I and II, we showed that inhibition of NF-κB reduced syndecan-4 shedding from cardiac myocytes and fibroblasts.…”
Section: Syndecan-4 Shedding In Cardiac Inflammation: Regulation Conmentioning
confidence: 99%
“…Syndecan shedding is highly regulated and dependent on the so-called sheddase enzymes. 188 In Paper I and II, we showed that inhibition of NF-κB reduced syndecan-4 shedding from cardiac myocytes and fibroblasts.…”
Section: Syndecan-4 Shedding In Cardiac Inflammation: Regulation Conmentioning
confidence: 99%
“…Changes in expression and function of these molecules are associated with and contribute to many pathophysiological conditions including malignancies and inflammation [1,2]. Syndecans are composed of a core protein comprised of an ectodomain, a transmembrane domain, and a conserved cytoplasmic domain, with three or more structurally diverse heparan sulfate chains.…”
mentioning
confidence: 99%
“…Syndecans are composed of a core protein comprised of an ectodomain, a transmembrane domain, and a conserved cytoplasmic domain, with three or more structurally diverse heparan sulfate chains. Four individual syndecans are expressed in a highly regulated tissue-, cell-, and development-specific manner [1,2]. As part of normal cell HSPG turnover, the intact ectodomain is shed from the cell surface, rendering HSPG soluble.…”
mentioning
confidence: 99%
See 2 more Smart Citations